Taxpayer Compliance: E-Filing, E-Billing, and the Moderating Role of Tax Awareness Campaigns - Melia Wida Rahmayani; Ayub Fahmi; Ita Latifah (AIBPM Publisher, 2026)
Digital tax administration is expected to improve taxpayer compliance; however, compliance challenges remain among taxpayers using electronic tax systems. This study aims to examine the effects of the e-filing and e-billing systems on individual taxpayer compliance and to investigate the moderating role of tax awareness campaigns in these relationships. A quantitative research design was employed using questionnaire data collected from 100 individual taxpayers registered at KP2KP Majalengka, Indonesia. The data were analyzed using Moderated Regression Analysis (MRA). The results indicate that e-filing has a positive and significant effect on taxpayer compliance (b = 0.342, p = 0.012), while e-billing also positively and significantly affects taxpayer compliance (b = 0.385, p = 0.008). Furthermore, tax awareness campaigns significantly strengthen the relationship between e-filing and taxpayer compliance (b = 0.274, p = 0.021) as well as the relationship between e-billing and taxpayer compliance (b = 0.298, p = 0.018). These findings suggest that digital tax systems are more effective when supported by continuous taxpayer education and awareness initiatives. The study highlights the importance of integrating technological innovation with tax socialization programs to improve taxpayer compliance.